Character Table Groups and Extracted Simple and Cyclic Polygroups - Sara Sekhavatizadeh; Mohammad Mehdi Zahedi; Ali Iranmanesh (Journal of the Indonesian Mathematical Society, 2020)
Let G be a finite group and \hat{G} be the set of all irreducible complex characters of G. In this paper, we consider <\hat{G}, *> as a polygroup, where for each chi_i ,chi_j in \hat{G} the product χ _{i} * χ_{j} is the set of those irreducible constituents which appear in the element-wise product χ_{i} χ_{j}. We call that \hat{G} simple if it has no proper normal subpolygroup and show that if \hat{G} is a single power cyclic polygroup, then \hat{G} is a simple polygroup and hence \hat{S}_{n} and \hat{A}_{n} are simple polygroups. Also, we prove that if G is a non-abelian simple group, then \hat{G} is a single power cyclic polygroup. Moreover, we classify \hat{D}_{2n} for all n. Also, we prove that \hat{T}_{4n} and \hat{U}_{6n} are cyclic polygroups with finite period.